Estratégias das incubadoras de empresas para difusão do empreendedorismo e da inovação: evidências das incubadoras de Minas Gerais - Guimarães, Victor Hugo de Souza (2023)
This dissertation presents a detailed investigation of key practices adopted by incubators located in Minas Gerais, Brazil, using the CERNE Model as a reference to identify and understand the fundamental strategies implemented by these institutions. The research focused on analyzing the websites of the incubators, examining how these entities disseminate information about their key practices. The study employed a methodological approach involving content analysis of the selected incubators' websites, with a focus on identifying and understanding the key practices advocated by the CERNE Model. Practices such as management, offered services, infrastructure, technical support, access to financial resources, among other fundamental aspects for the development of startups and innovative ventures, were considered. The results revealed significant variability in how Minas Gerais' incubators communicate and highlight their key practices on their websites. Some institutions showed a clear emphasis on certain practices, while others provided more comprehensive information about their support for entrepreneurs. It is concluded that analyzing the incubators' websites in accordance with the CERNE Model is important to understand not only the adopted key practices but also the effectiveness of communicating these practices to potential entrepreneurs. This study contributes to the understanding of the strategies used by incubators in promoting their support offerings and essential services for the growth of startups and innovative ventures.